An analysis of 1000 consecutive cases seen at the ml India Institute of Speech and Hearing - P, Rama Mohan Babu; Satyendru Kumar (Journal of All India Institute of Speech and Hearing, 1972)
It is the purpose of this paper to analyse 1000 cases seen at the All India Institute of Speech and Hearing, for variables like sex, age, number of siblings in the family, position of the case among the siblings, family history, consanguinity, who referred the case to our Institute, whether he was advised therapy or not, and if so, whether he attended therapy or not